The new immunosuppression: intervention at the dendritic cell-T-cell interface. - Paterson, A; Yates, S; Nolan, K; Waldmann, H (2005)
Dendritic cells (DCs) play an important role in initiating and directing T-cells towards immunity or tolerance. An important aim of emerging immunosuppressive strategies is to ensure that antigen is perceived in a 'tolerogenic context'. This would have obvious benefit in minimising the need for long-term drug maintenance in organ transplantation, hypersensitivity and autoimmune diseases. Here we review the biology of the interplay between the DC and T-cell, with a specific focus on therapeutic drugs targeting molecules that effect their interaction and function.